Contribuições da ética da psicanálise à política pública de saúde - Fernandes, Verônica Alves (2013)
The present study aims to create a reflecion on how the psychoanalytic theory supported in clinical practice and based on ethics of well say desire can be as a beacon for institutions on showing other ways of dealing with the ideals, values and laws instituted in the social field. We start with a brief history of the Health Reform Movement in Brazil and how it has culminated with the establishment of the SUS. Then, we present the basic health care foccus (ABS) and we questioned the malaise that is present in the relationships developed between patients and healthcare professionals at UBS, as well as the barriers and obstacles that exist for the realization and consolidation on adverstising health prevention actions performed at this services centers. A literature review allowed us to verify the insertion of psychoanalysis in different health services, particularly in mental health network and hospital care, noting the importance of the listening of the singularity of the subject in these spaces and the effects of shifts in rigid positions and ideals of patients, the team of health professionals and therefore, the institutional relations. We used the theoretical and methodological psychoanalytic speech oriented by the teachings of Freud and Jacques Lacan to demonstrate the contribution of psychoanalysis to the ethics of public health, including primary care services, taking relevance on the fact that psychoanalysis does not flinch when faces the speech of the subject, only element that can make an exception and break the homogeneity and standardization of all that generalizable knowledge, seeking universality, ultimately crystallize on the subject and in its history. Giving voice to the subject seems essential if we are to advance the goals of health initiatives that aim a change on the territories of the ones that live in large urban centers, which, therefore, must go beyond the effects of interventions in socio-economic and culture where the community and the individual are